The Impact of Online Learning on the Learning Motivation of Junior High School Students - Pinkan Harjudanti (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2021)
Online learning is a basic need of education in the 21st century. The benefits of online learning are felt in the continuity of education during the Covid-19 pandemic. This study aims to examine the impact of online learning on the learning motivation of Junior High School (SMP) students. The results of the research discussion indicate that online learning has advantages, namely 1) as a medium to encourage independent learning; 2) as an effort to modernize the concept of education in the 21st century; 3) increasing the intensity of the interaction between teachers and students; 3) allows for an interaction that is not limited to space and time, and 4) meaningful learning. The impact of online learning on student learning motivation tends to be negative due to the unpreparedness of various parties, including teachers, parents, students, and schools. Early adolescents who need direct guidance, direction, and motivation must lose control due to reduced direct interaction with the teacher. The monotonous implementation of online learning, lack of direction and supervision, pressure for students to study from home, and low teacher innovation are the main causes of decreased learning motivation due to online learning.